2013
DOI: 10.1523/jneurosci.0019-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Postsynaptic Density-93 Isoforms in Regulating Synaptic Transmission

Abstract: In the postsynaptic density of glutamatergic synapses, the discs large (DLG)-membrane-associated guanylate kinase (MAGUK) family of scaffolding proteins coordinates a multiplicity of signaling pathways to maintain and regulate synaptic transmission. Postsynaptic density-93 (PSD-93) is the most variable paralog in this family; it exists in six different N-terminal isoforms. Probably because of the structural and functional variability of these isoforms, the synaptic role of PSD-93 remains controversial. To accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 50 publications
3
76
2
Order By: Relevance
“…Previous experiments (Elias et al, 2006) have reported that PSD-93 and PSD-95 each account for half of AMPAR-mediated transmission (but see Krüger et al, 2013), while SAP102 plays a compensatory role if both PSD-93 and PSD-95 are lost. Knockdown of PSD-93 or PSD-95 has been reported to have either no (Elias et al, 2006) or minimal effect (Ehrlich et al, 2007) on NMDAR currents.…”
Section: Resultsmentioning
confidence: 98%
“…Previous experiments (Elias et al, 2006) have reported that PSD-93 and PSD-95 each account for half of AMPAR-mediated transmission (but see Krüger et al, 2013), while SAP102 plays a compensatory role if both PSD-93 and PSD-95 are lost. Knockdown of PSD-93 or PSD-95 has been reported to have either no (Elias et al, 2006) or minimal effect (Ehrlich et al, 2007) on NMDAR currents.…”
Section: Resultsmentioning
confidence: 98%
“…The PSD‐93 gene is the most complex among the DLG‐MAGUKs; it codes for the highest number of N‐terminal isoforms (Parker et al , ; Krüger et al , ). Consequently, the analysis of PSD‐93 KOs has uncovered multiple, and partly conflicting results on PSD‐93‐mediated regulation of AMPARs.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the analysis of PSD‐93 KOs has uncovered multiple, and partly conflicting results on PSD‐93‐mediated regulation of AMPARs. It was consistently observed that PSD‐95 and PSD‐93 isoforms share some redundancy in regulating AMPAR function, when one is replaced by another or over‐expressed (Elias et al , ; Krüger et al , ). However, results on the loss of PSD‐93 function vary.…”
Section: Resultsmentioning
confidence: 99%
“…Hippocampal cultures were prepared from P0–1 mice as described (Krüger et al, 2013). For immune staining, neurons were fixed with 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoprecipitates were separated by Bis-Tris gels (Bonnet et al, 2013), transferred onto nitrocellulose and analyzed using standard procedures (Krüger et al, 2013). …”
Section: Methodsmentioning
confidence: 99%